An experimental evaluation of the effects of sea depth, wave energy converter's draft and position of centre of gravity on the performance of a point absorber wave energy converter. Issue 2 (4th May 2017) - Alamian, Rezvan; Shafaghat, Rouzbeh; Bayani, Rasoul; Amouei, Amir Hossein
ABSTRACT: In this paper, the effects of sea depth, wave energy converter's (WEC's) draft and position of centre of gravity on the performance of a point absorber WEC are examined using an experimental study. By considering the general cubic shape for the WEC, the tests are implemented in the experimental wave tank. In this context, by creating waves with different amplitudes and periods, evaluation is conducted in three different magnitudes for each parameter. WEC oscillations in the directions of heave, surge and pitch are measured and compared. Furthermore, an optimised model for building a full-scale WEC for operating in the Caspian Sea environment is studied and proposed. Experimental test results show that the model with least draft and least distance between the position of centre of gravity and still water level and also installed in the deepest sea is the best model to be installed in the Caspian Sea.